English Interference on Balinese Dialect in Sumberkima Village - Pinatih, I Kadek Ngurah Yudha Darma Laksana (Universitas Pendidikan Ganesha, 2022)
In the phenomenon of language, speakers who can speak two or more languages will often incorporate or mix elements from their first language into their second language. This causes language interference. This phenomenon becomes interesting to study further. This research aims to analyse the interference Phonology of Balinese Dialect on English. The type of this research is qualitative research. The method used in this study is descriptive qualitative method. Collecting data for this research was conducted by asking for a native speaker in Sumberkima village to read English text and the researcher will record it. The text was randomly chosen by the researcher so that the target won’t have time to learn how to pronounce every word on the text. The method used to analyse the data is the equivalent method, namely the articulatory phonetic equivalent method. The method used to deliver the result of the research is formal and informal. Based on the research result, the researcher found phonological interference on Indonesian with the Balinese dialect to English. The interference heard clearly on hisser and other sounds. That interference occurs in the sound o and d in the starting position, the sound of z, f, u, and r in the final position, the sound of v in the initial and end, I sound in the middle, also sound that ended with morphemes.